2000
DOI: 10.1538/expanim.49.9
|View full text |Cite
|
Sign up to set email alerts
|

Histological Analysis of Murine Colitis Induced by Dextran Sulfate Sodium of Different Molecular Weights.

Abstract: Abstract:In this study, we examined the relationship between the molecular weight of dextran sulfate sodium (DSS) and the features of colitis in a DSS-induced mouse model of human ulcerative colitis. DSS at three different molecular weights, 5 kD, 40 kD and 500 kD, was used in this study. DSS was administered in drinking water at 5% (w/v) to 6-7-weekold female BALB/c mice. After 7 days of treatment with DSS, the large intestine was examined histopathologically. Colitis was characterized by a loss of crypts, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 25 publications
8
133
0
Order By: Relevance
“…The features of colitis that we observed in CVz mice with colitis induced by 5% DSS were similar to those described in previous reports [6,21]. However, when compared to our previous data using BALB/c mice [21], the CVz IQI/Jic mice rapidly developed intestinal erosion, whereas BALB/c mice had only mild crypt loss on day three after administration of 5% DSS [13,14]. In BALB/c mice, intestinal erosion was first noticed on day five following dosage with DSS [13,14].…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…The features of colitis that we observed in CVz mice with colitis induced by 5% DSS were similar to those described in previous reports [6,21]. However, when compared to our previous data using BALB/c mice [21], the CVz IQI/Jic mice rapidly developed intestinal erosion, whereas BALB/c mice had only mild crypt loss on day three after administration of 5% DSS [13,14]. In BALB/c mice, intestinal erosion was first noticed on day five following dosage with DSS [13,14].…”
Section: Figsupporting
confidence: 90%
“…Bylund-Fellenius et al [5] have suggested that degradation of DSS by intestinal microflora is a likely reason for this difference. However, we believe that this is unlikely because in one of our previous studies we did not detect any small fragments of DSS in the feces of mice on day three after administration of 5% DSS on polyacrylamide gels [14]. Certain bacterial strains produce dextranase, which hydrolyzes the α-1, 6 glycosidic linkage [12,27].…”
Section: Figmentioning
confidence: 99%
“…Thus, the DSS treatment used in our study appears to impair neurogenic responses such as spontaneous and nicotine responses without markedly changing muscular responses. The expression of molecules such as inflammatory cytokines and NO synthase induced by DSS treatment was dependent on the progress of colitis which was modulated by experimental conditions such as species including strains of mice, DSS dose and type, and treatment period (20,25,30,32). The inflammation, when severe, appeared to impair not only neuronal but also muscular functions.…”
Section: Changes Of Nicotine-induced Response In the Dsstreated Micementioning
confidence: 99%
“…Colitis was induced in mice by giving 3% (wt/vol) DSS (molecular mass 30 -40 kDa; ICN Biomedicals, Aurora, OH) in drinking water ad libitum as reported by others (26,35,48). Importantly, 30-to 40-kDa DSS was utilized in this study because it is known to induce more severe colitis than 5-kDa DSS and 500-kDa DSS (25). For each mouse, weight and rectal bleeding were determined every day following the introduction of DSS.…”
Section: Synthesis Of P2281mentioning
confidence: 99%